Pea and lupin protein ingredients: New insights into endogenous lipids and the key effect of high-pressure homogenization on their aqueous suspensions. (August 2023) - Keuleyan, Eléna; Gélébart, Perrine; Beaumal, Valérie; Kermarrec, Alice; Ribourg-Birault, Lucie; Le Gall, Sophie; Meynier, Anne; Riaublanc, Alain; Berton-Carabin, Claire
Abstract: The incorporation of plant protein ingredients in foods is a means to promote the transition to vegetable proteins. Pea and lupin meet sustainability demands and their protein ingredients display promising technological properties, yet sometimes poor functionalities. However, the involved mechanisms are still unclear, partly because comprehensive and systematic characterization of those ingredients in terms of composition and physicochemical properties is still lacking. In this work, commercial protein fractions of pea and lupin (one isolate and one concentrate for each) were thoroughly characterized. A high-pressure homogenization (HPH) treatment was applied to their aqueous suspensions (pH 7.0) to improve their dispersibility. Although isolates displayed a higher protein content (up to 72 g/100 g (d.m.) against 39 g/100 g (d.m.) for the concentrates, with respective specific N factors), their solubility (i.e., the proteins remaining in the supernatant after centrifugation) was lower than for the concentrates (15–49 wt% of the total proteins, against 65 wt%). Substantial amounts of endogenous lipids in the powders were measured after chloroform/methanol extraction (3.4–10.3 g/100 g (d.m.)), of which about half were phospholipids. For all ingredients, detailed microscopic investigations (including confocal fluorescence microscopy), and light scattering measurements showed that HPH was useful to break down large powder grains. Thus, it altered the colloidal structures present, released endogenous lipid assemblies and enhanced protein solubility. Those new insights into the non-protein composition of plant protein fractions and their behaviour in aqueous media are key for improving their functionalities and facilitating food products' rational formulation. Graphical abstract: Image 1 Highlights: The comprehensive composition of plant protein ingredients is so far largely overlooked. Endogenous lipids are present in commercial pea and lupin protein powders. These endogenous lipids include a substantial amount of surface-active phospholipids. Homogenization disrupts large powder aggregates and enhances their dispersibility. This treatment also releases lipids as small colloidal structures in suspension.